2023
DOI: 10.13057/biodiv/d240625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different extraction solvents on the yield and enzyme inhibition (a-amylase, a-glucosidase, and lipase) activity of some vegetables

Abstract: Abstract. Maser WH, Maiyah N, Nagarajan M, Kingwascharapong P, Senphan T, Ali AMM, Bavisetty SCB. 2023. Effect of different extraction solvents on the yield and enzyme inhibition (a-amylase, a-glucosidase, and lipase) activity of some vegetables. Biodiversitas 24: 3320-3331. The present study investigated the in vitro inhibition of a-amylase, a-glucosidase, and lipase, and antioxidant activities (DPPH, metal chelating, and FRAP) of Allium cepa L., Apium graveolens L., Coriandrum sativum L., and Petroselinum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…4 ). In one recent study, Maser et al (2023b) also reported a positive correlation in GLV extracts between metal chelating activity and TPC ( P <0.01), which suggests that phenolic compounds such as flavonoids, condensed tannins, and phenolic acids may significantly contribute to metal chelation. Similarly, Arogundade et al (2023) found that metal chelating ability increased with the addition of plantain flour and bambara groundnut blends to biscuits.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…4 ). In one recent study, Maser et al (2023b) also reported a positive correlation in GLV extracts between metal chelating activity and TPC ( P <0.01), which suggests that phenolic compounds such as flavonoids, condensed tannins, and phenolic acids may significantly contribute to metal chelation. Similarly, Arogundade et al (2023) found that metal chelating ability increased with the addition of plantain flour and bambara groundnut blends to biscuits.…”
Section: Resultsmentioning
confidence: 86%
“…GLV powder was prepared using a method described by Maser et al (2023b) . Briefly, GLVs were first dehydrated in a WRH-100 drier (IKE Industrial Co., Ltd.) at 45°C until they reached a constant weight.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations